Konsep Akad Komisen Dalam Islam Dan Aplikasinya Dalam Sistem Muamalat Semasa: Commission Concept in Islam and Its Application in Current Muamalat System - Wan Adnan, Wan Azlan; Ali, Nor Aini (Online Journal of Research in Islamic Studies, 2020)
Commissions are a form of payment for services commonly used in transactions involving the business sector, banking, financial agencies and day-to-day transactions. It is also known by various terms such as wages, rewards, fees, bonuses or prizes. Commission is theoretically the subject of debate by previous and contemporary scholars in various forms of contract related to it. Although it is included in the category of wages but if viewed in more detail there are differences in some aspects and orientation of its use. This article is a review of the literature related to the concept of commission agreement based on the debate of previous and recent scholars. The research methodology using the literature review method takes the library research approach. The discussion is a highlight of the collection of writings and studies that have to do with the topic. The discussion also covers how commissions are implemented practically in various current financial transactions.